1998
DOI: 10.1007/s004310050796
|View full text |Cite
|
Sign up to set email alerts
|

Does the long-term clinical course of type I diabetes mellitus differ in patients with prepubertal and pubertal onset? Results of the Berlin Retinopathy Study

Abstract: Adolescents with a pubertal onset of type I diabetes have a more benign long-term course of the disease demonstrating better glycaemic control and lower insulin requirements, although the presentation of the disease at onset and its course during the first 6 years are not different from those of children with a prepubertal manifestation of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
3
23
1
Order By: Relevance
“…Under real-life conditions, there is no glycaemic threshold of HbA 1c between 6.0% (42.1 mmol/mol) and 7.5% (58.5 mmol/mol), as suggested by the DCCT and other studies [20,28]. Thus, our field study supports the guideline that the therapeutic goal should be the best achievable glycaemic target.…”
Section: Discussionsupporting
confidence: 74%
“…Under real-life conditions, there is no glycaemic threshold of HbA 1c between 6.0% (42.1 mmol/mol) and 7.5% (58.5 mmol/mol), as suggested by the DCCT and other studies [20,28]. Thus, our field study supports the guideline that the therapeutic goal should be the best achievable glycaemic target.…”
Section: Discussionsupporting
confidence: 74%
“…However, in the population at risk, i.e., with a diabetes duration Ͼ15 years, a total of 33 of 4,414 (0.7%) of the patients had developed ESRD due to diabetic nephropathy. The median time of follow-up in this cohort was 21 years (range [15][16][17][18][19][20][21][22][23][24][25][26][27] and the median time from onset of diabetes to ESRD was 20 years (range [15][16][17][18][19][20][21][22][23]. There was no significant difference in median time of follow-up in the three different age-at-onset strata (20.3 [range 15-27], 20.5 [15][16][17][18][19][20][21][22][23][24][25][26][27], 20.4 [15][16][17][18][19][20][21][22][23][24][25][26]…”
Section: Resultsmentioning
confidence: 96%
“…Puberty, in addition to frequently noted deterioration of glycemic control, is characterized by rapid growth and hormonal changes, all factors that could promote the development of chronic diabetes complications (6 -8). Thus, some clinical studies (6,9 -12) but not all (13)(14)(15)(16)(17) suggest that prepubertal diabetes duration may contribute less to the development of microvascular complications than pubertal and postpubertal duration. In addition, there are studies that have suggested that an onset of diabetes in the youngest age-group, age Ͻ5 years, may delay development of chronic diabetes complications such as microalbuminuria and retinopathy (18 -21).…”
mentioning
confidence: 99%
“…However, children who were younger than 5 years at the onset of diabetes experience the same hormonal changes during puberty as those diagnosed with diabetes later in childhood. Additionally, it seems that children with an onset of diabetes at a very young age do not maintain good glycemic control during the pubertal years (38), although there are few longitudinal studies that address this question. It is, however, unclear if hormonal changes of the years before and during puberty occurring simultaneously with the onset of diabetes have an impact on the increased risk of DN later in life.…”
Section: Discussionmentioning
confidence: 99%